PENGARUH FUNGSI AUDIT INTERNAL TERHADAP FEE AUDITOR EKSTERNAL - Erlina Dyah Hapsari; Herry Laksito (Diponegoro Journal of Accounting, 2013)
Understanding the relationship between a firm’s internal audit function and its external auditor fees is important. It has economic implications for firms and external auditors, particularly given that internal and external auditors both serve as monitoring mechanisms of a firm. This study examine the relationship between a firm’s internal audit function and its external auditor fee. It uses secondary data from annual reports of non-financial companies which listed on Bursa Efek Indonesia in 2010-2011. This study used purposive sampling method and used multiple linear regression as the analysis instrument. Before being conducted the regression test, it is examined by using the classical assumption tests. The results of this study indicate that internal audit function significantly influence the external auditor’s fees. Firms with active internal audit functions have higher audit fees, as a consequences higher complexity of external auditor duty. It means that higher responsibility of external auditor on determine the relevances of internal audit function related to firm’s internal control structure and its influences to financial statement or misstatement potential of financial statements, resulting in higher audit fees.